Do different pathologies of adult spinal deformity (idiopathic lumbar scoliosis against de novo lumbar scoliosis) affect preoperative and postoperative selfimage? - hiroshi Taniwaki; Akira Matsumura; Yuki Kinoshita; Masatoshi Hoshino; Takashi Namikawa; Yusuke Hori; Hiroaki Nakamura (Asian Spine Journal, 2024)
Study Design Retrospective single-center study. Purpose This study aimed to examine the factors associated with the self-image domain of the Scoliosis Research Society-22 revised (SRS-22r) in patients who underwent corrective surgery for adult idiopathic scoliosis (AdIS). Overview of Literature Adult spinal deformity (ASD) can be classified into AdIS and de novo scoliosis. However, no studies have investigated the effect of different ASD pathologies on self-image. Methods This study enrolled 60 patients who underwent corrective surgery and were followed up for >2 years postoperatively. AdIS was defined as adolescent idiopathic scoliosis in patients who had no history of corrective surgery, had a primary thoracolumbar/lumbar (TL/L) curve, and were ≥30 years old at the time of surgery. Results The AdIS (n=23; mean age, 53.1 years) and de novo (n=37; mean age, 70.0 years) groups were significantly different in terms of the main thoracic and TL/L curves, sagittal vertical axis, thoracic kyphosis, and thoracolumbar kyphosis preoperatively. The scores in the self-image domain of the SRS-22r (before surgery/2 years after surgery [PO2Y]) were 2.2/4.4 and 2.3/3.7 in the AdIS and de novo groups, respectively, and PO2Y was significantly different between the two groups (p<0.001). Multivariate regression analysis revealed that AdIS was an independent factor associated with self-image at PO2Y (p=0.039). Conclusions AdIS, a spinal deformity pathology, was identified as a significant factor associated with the self-image domain of SRS-22r in patients who underwent corrective surgery. AdIS is not solely classified based on pathology but also differs in terms of the clinical aspect of self-image improvement following corrective surgery.